Agregando serviço e produzindo vestuário para Pessoas com Deficiência: estratégia de diferenciação para confecções brasileiras (ModaPalavra e-periódico, 2014)
Brazil has a large manufacturing hub of fashion and a significant portion of the population with disabilities, about it this article aims to present a strategy and competitive differentiation for Brazilian confections, from the service offer of Assistive Fashion Consultant, producing garments for customers with disabilities focusing on appoach social market. Arise management concepts design and innovation in clothing from the system, processes, products and services in the field of fashion, as well as a survey of service in Assistive Technology, presents a service that aggregates sales and after-sales service, called Consultant of Assistive Fashion. This professional has the function to assess the need for the client clothing, their measures and assistive technology that can be aggregated clothes for your life to be more comfortable and independent, provides clothing, delivery, teaches the use and comes in after sales.